Automatic idea generation and analysis using NLP and ML techniques - Liu, Haixia (2019)
Ideas are the fundamental way in which information is conveyed in written text. This research investigates the discovery and extraction of ideas from corpuses of scientific literature. There are several elements to this work: (1) the functional definition of ideas; (2) the computation of novel ideas; (3) the representation of ideas; (4) the construction of a ground truth dataset; and (5) the use of citations as an idea container.